Go be a Writer! Book Review - Ramzy, Miriam (Emerging Trends in Education, 2018)
This review explores the book Go be a Writer! Expanding the Curricular Boundaries of Literacy Learning with Children, written by professor and researcher Candace R. Kuby, and teacher Tara Gutshall Rucker. The review begins by explaining how the authors reimagined the writing instruction in Tara’s classroom, which they named ‘writer’s studio’. This is followed by a summary of the book’s nine chapters, organized into three sections: an explanation of the theoretical framework and eight guiding concepts, a look at actual writing projects developed by Tara’s grade one and two students, and a conclusion, aligning writer’s studio with the Common Core State Standards (CCSS). The structure and style of the writing of this book is unique in that Candace and Tara use multiple modes to communicate their ideas and learning, including images, changes in fonts, symbols, and shifts in genre. I would recommend this book for many audiences, including teachers, administrators, professors, and pre-service teachers as a presentation of a new way to think about how we can teach writing in schools.